Enhancing Fraud Detection in Financial Transactions through Cyber Security Measures - Vishva Gandhi; Gajjar, Tirthesh (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The digitization of financial systems has brought unprecedented convenience, but it has also increased fraud. This article explores the important intersection of cybersecurity and fraud detection in financial transactions. As the need to effectively combat fraud increases, he explores a variety of cybersecurity approaches and technologies. This article examines advanced technologies such as data mining, machine learning, biometric authentication, and blockchain through a comprehensive review of existing literature. It also highlights the challenges and limitations faced by modern fraud detection methodologies, including sophisticated cyberattacks and regulatory issues. By recognizing these challenges, stakeholders can work to implement holistic solutions that address both technical and regulatory aspects. Ultimately, the purpose of this document is to provide practical guidance for strengthening fraud detection capabilities, strengthening financial systems, and protecting consumer interests in the digital economy.